Efficient In Vitro Full‐Sense‐Codons Protein Synthesis (Adv. Biology 10/2022). Issue 10 (21st October 2022) - Wu, Yang; Tang, Mengtong; Wang, Zhaoguan; Yang, Youhui; Li, Zhong; Liang, Shurui; Yin, Peng; Qi, Hao
Abstract : Efficient Protein Synthesis In article 2200023, Qi and co‐workers show that by orthogonal degradation of the targeted protein, both essential and alternative termination types of machinery are completely removed from E. coli cell extract. Furthermore, a total of 153 engineered tRNAs are screened for efficient all stop‐codons decoding to construct a codon‐dependent termination defect in vitro protein synthesis with all 64 sense‐codons, iPSSC, which holds potential in building artificial protein synthesis beyond the cell.